1992
DOI: 10.1073/pnas.89.19.9247
|View full text |Cite
|
Sign up to set email alerts
|

"Enzymogenesis": classical liver alcohol dehydrogenase origin from the glutathione-dependent formaldehyde dehydrogenase line.

Abstract: Analysis of the activity and structure of lower vertebrate alcohol dehydrogenases reveals that relationships between the classical liver and yeast enzymes need not be continuous. Both the ethanol activity of class I-type alcohol dehydrogenase (alcohol:NAD+ oxidoreductase, EC 1.1.1.1) and the glutathione-dependent formaldehyde activity of the class rI-type enzyme [formaldehyde:NAD+ oxidoreductase (glutathione-formylating), EC 1.2.1.1] are present in liver down to at least the stage of bony fishes (cod liver: et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 28 publications
0
68
0
Order By: Relevance
“…The expansion of single-copy genes in vertebrates has been dated in a variety of gene families (for reviews see Lundin 1993;Skrabanek and Wolfe 1998). Irrespective of the mechanism, duplications are responsible for the extant gene families and isoforms from fish to mammals (Ohno 1970;Lundin 1993) and are believed to be related to the gains in complexity which have allowed the acquisition of new functions through enzymogenesis (Danielsson and Jörnvall 1992) and changes in gene regulation (for a review see Shimeld 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expansion of single-copy genes in vertebrates has been dated in a variety of gene families (for reviews see Lundin 1993;Skrabanek and Wolfe 1998). Irrespective of the mechanism, duplications are responsible for the extant gene families and isoforms from fish to mammals (Ohno 1970;Lundin 1993) and are believed to be related to the gains in complexity which have allowed the acquisition of new functions through enzymogenesis (Danielsson and Jörnvall 1992) and changes in gene regulation (for a review see Shimeld 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The class 1 enzyme, the "classical" ethanol-active form, has evolved rapidly and exhibits a considerable variability among species (Danielsson et al 1994a). ADH class 3 [glutathione-dependent formaldehyde dehydrogenase (Koivusalo et al 1989)] is present in prokaryotes and in all eukaryotes and appears to be the ancestral form from which the other vertebrate ADH classes emerged (Danielsson and Jörnvall 1992;Danielsson et al 1994a;Cañestro et al 2000) through gene duplications during early vertebrate radiation. Supporting evidence comes from the apparent absence of an ethanol-active class 1 form in lines originating before the bony fish (Danielsson et al 1994b) and the presence of a class 1/3-mixed form in bony fish (Danielsson et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…brates [6], apparently illustrating enzymogenesis of novel ethanol dehydrogenase activity from the ancient formaldehyde dehydrogenase [7]. At least four further classes of alcohol dehydrogenase exist, indicating still more gene duplications, giving rise to classes I1 [2], IV [S], V [9] and VI [lo], of which just a few variants are known, not allowing for extensive conclusions on their patterns of divergence.…”
mentioning
confidence: 99%
“…4). In contrast, for class 111, w e thus far have only one reported isozyme pair (h/l) [6]. Therefore …”
Section: Isozyme Occurrencementioning
confidence: 88%
“…Since conditions for traditional class and isozyme separations on ion exchangers did not produce separation of these forms, we decided to evaluate i sozyme differences by determination of the two isozyme primary structures in mixture. Although cumbersome and involving more work, this approach has the advantage of not risking loosing any forms, which has been a problem in other alcohol dehydrogenases of lower vertebrates, where initial studies also indicated isozymes which were difficult to separate, and where the presence of dimers in selective combinations were found [6].…”
Section: ~4mentioning
confidence: 99%